The success of halal food MSME business growth: application of payment technology and spiritual entrepreneurship / Tri Atmaja Pramudita Wisnu Kusuma, Satria Bangsawan and Mahrinasari MS - Wisnu Kusuma, Tri Atmaja Pramudita; Bangsawan, Satria; MS, Mahrinasari (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2025)
The success of the growth of halal food MSMEs through the level of technology adoption and internalization of spiritual values faces problems where there are technical constraints such as limited internet infrastructure, transaction security, and digital literacy which are the main obstacles to the use of QRIS by MSMEs in less digitized areas. In addition, spiritual values in business require a deep understanding of how these values can be translated into ethical and sustainable business practices, which are often difficult due to the lack of guidance and concrete examples. The purpose of this study was to see the relationship between payment technology, namely QRIS and spiritual entrepreneurship on the development and the success of the growth of Halal Food MSMEs in Lampung Province. The research methodology used in this study was quantitative using the SmartPLS 3.0 software. Primary data collection was carried out by taking a sample of respondents, namely Halal Food MSME business actors in Lampung Province, Indonesia through a purposive sampling method. A total of 200 samples were used for this study. Data were obtained through the use of Google Form, with indicator assessments carried out using the Likert Scale. The findings of the study indicated a relationship between payment technology, namely QRIS and spiritual entrepreneurship on the development of the success of the growth of Halal Food MSMEs in Lampung Province.